Umami : unlocking the secrets of the fifth taste - Mouritsen, Ole G. (Arts and traditions of the table., 2014)
In the West, we have identified only four basic tastes?sour, sweet, salty, and bitter?that, through skillful combination and technique, create delicious foods. Yet in many parts of East Asia over the past century, an additional flavor has entered the culinary lexicon: umami, a fifth taste impression that is savory, complex, and wholly distinct. Combining culinary history with recent research into the chemistry, preparation, nutrition, and culture of food, Mouritsen and Styrbk encapsulate what we know to date about the concept of umami, from ancient times to today. Umami can be found in.